Golden Canna: Canna flaccida - Edward F. Gilman; Carl J. Della Torre; Lyn A. Gettys (EDIS, 2015)
Golden canna is a native wetland plant with bright yellow flowers that can be found throughout most of Florida. This revised 4-page facts sheet details the golden canna’s biology, distribution and habitat, propagation, pests and diseases, and landscaping and other uses. Written by Edward F. Gilman, Carl J. Della Torre III, and Lyn A. Gettys, and published by the UF Department of Environmental Horticulture, June 2015.